Stinky Spike and the Royal Rescue : Stinky Spike #2 - Meisel, Peter, 1985-; Meisel, Paul (New York : Bloomsbury, 2017)
"Stinky Spike the dog and Captain Fishbeard the pirate are thick as thieves now that Spike has proved his treasure-sniffing ability. When Spike and his crew come across a sign offering a reward for finding the Princess's lost poodle, they can hardly resist. Surely finding a fluffy royal pooch can't be very difficult? When blundering pirates are involved, things never go according to plan"--
Keywords: Dogs -- Fiction; Smell -- Fiction; Pirates -- Fiction; JUVENILE FICTION / Readers / Chapter Books; JUVENILE FICTION / Animals / Dogs; JUVENILE FICTION / Action & Adventure / Pirates; JUVENILE FICTION / Humorous Stories; Humorous fiction